Tumor-infiltrating lymphocytes in melanoma: diagnostic and prognostic implications from biopsy to circulation - Hussain Noorwali (The Journal of Liquid Biopsy, 2025)
Melanoma is a highly aggressive skin cancer that arises from melanocytes and presents considerable clinical challenges due to its strong metastatic capacity and ability to evade the immune system. Tumor-infiltrating lymphocytes (TILs) reflect the host's immune activity within the tumor microenvironment and have gained recognition as important biomarkers for both diagnosis and prognosis in melanoma. A higher density of TILs—particularly CD8+ cytotoxic T cells—is associated with better overall survival and reduced risk of recurrence. Histopathological assessment of TILs, including classification systems like the Clark model, plays a key role in risk stratification, particularly in early-stage melanoma.Meanwhile, peripheral blood T-cell profiling offers a non-invasive approach to assess systemic immune status. Circulating T-cell subsets and their expression of activation or exhaustion markers (e.g., PD-1, CTLA-4) reflect tumor immune dynamics and may serve as potential indicators of disease progression or prognosis.Despite promising data, heterogeneity in TIL composition and peripheral immune profiles challenges consistent interpretation and clinical implementation. Future efforts should focus on standardizing TIL assessment, integrating tissue and blood immune markers, and leveraging computational tools to develop robust predictive models. This integrated immunological approach holds potential to refine melanoma prognosis and improve risk stratification.This review aims to provide an updated and comprehensive overview of the diagnostic and prognostic significance of TILs and peripheral T-cell markers in melanoma. By synthesizing current evidence and addressing key limitations, it underscores the importance of immune profiling in advancing melanoma evaluation and guiding future research directions.